Wave-absorbing material, preparation method of wave-absorbing material, polyurethane composite wave-absorbing material and preparation method of polyurethane composite wave-absorbing material

By loading nickel selenide and cobalt selenide on carbon nanotubes, forming a heterojunction structure and compounding it with a polyurethane matrix, the problem of insufficient performance of traditional electromagnetic wave absorption materials is solved, and efficient electromagnetic wave absorption and good environmental adaptability are achieved.

CN120137266APending Publication Date: 2025-06-13SHANDONG XIEHE UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510506899.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorption materials have limitations in electromagnetic wave absorption performance and cannot meet the needs of diversified and harsh application environments.

Method used

Carbon nanotubes are used as carriers to load nickel selenide and cobalt selenide to form a heterojunction structure absorber, and composite them with a polyurethane matrix to prepare a polyurethane composite absorber.

Benefits of technology

By introducing heterostructured nickel selenide cobalt selenide and highly conductive carbon nanotubes, the electromagnetic wave absorption performance of the material is significantly improved and good environmental adaptability and flexibility are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137266A_ABST
    Figure CN120137266A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wave-absorbing materials, and particularly relates to a wave-absorbing material and a preparation method thereof, and a polyurethane composite wave-absorbing material and a preparation method thereof. The invention provides a wave-absorbing material. The wave-absorbing material comprises a carbon nano tube and selenide loaded on the carbon nano tube, the selenide comprises nickel selenide and cobalt selenide; a heterojunction structure is arranged between the nickel selenide and the cobalt selenide. According to the invention, a heterostructure is formed among selenide, and the structure can effectively enhance interface polarization of the material and promote an internal energy dissipation mechanism, so that electromagnetic waves are quickly converted into heat to be lost when passing through a heterointerface, and the electromagnetic wave absorption capability of the material can be optimized to a great extent; the wave-absorbing material not only can significantly improve the electromagnetic wave absorption performance, but also can maintain good environmental adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microwave absorbing materials, and particularly relates to a microwave absorbing material and a preparation method thereof, a polyurethane composite microwave absorbing material and a preparation method thereof. Background Art

[0002] With the rapid development of communication technology, the problems of electromagnetic interference and pollution have become increasingly serious, resulting in a sharp increase in the demand for high-performance electromagnetic wave absorbing materials. Traditional electromagnetic wave absorbing materials mainly consist of inorganic magnetic or conductive metal materials, and these materials have limitations in electromagnetic wave absorption performance and cannot meet the requirements of current diverse and harsh application environments. Summary of the Invention

[0003] The purpose of the present invention is to provide a microwave absorbing material and a preparation method thereof, a polyurethane composite microwave absorbing material and a preparation method thereof.

[0004] In order to achieve the above purpose, the present invention provides the following technical solutions:

[0005] The present invention provides a microwave absorbing material, which includes carbon nanotubes and selenides loaded on the carbon nanotubes; the selenides include nickel selenide and cobalt selenide;

[0006] There is a heterojunction structure between the nickel selenide and the cobalt selenide.

[0007] Preferably, the molar ratio of the nickel selenide to the cobalt selenide is 1:1;

[0008] The mass percentage content of the selenide in the microwave absorbing material is 40-90%.

[0009] The present invention also provides a preparation method of the microwave absorbing material according to the above technical solution, including the following steps:

[0010] Disperse nickel salt and cobalt salt in water to obtain a dispersion;

[0011] Add ethylenediamine to the dispersion and perform the first stirring, then add a selenium source and perform the second stirring to obtain a mixed solution;

[0012] Mix the aqueous dispersion containing carbon nanotubes and the mixed solution, and perform a hydrothermal reaction to obtain the microwave absorbing material.

[0013] Preferably, the nickel salt includes at least one of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt includes at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; the molar ratio of the nickel salt to the cobalt salt is 1:1;

[0014] The dispersion is carried out under ultrasonic conditions, and the ultrasonic time is 0.5-3 h;

[0015] The molar ratio of the nickel salt to ethylenediamine is 1:1.5 to 7.5; the time of the first stirring is 1 to 3 h;

[0016] The selenium source includes at least one of sodium selenite and selenium dioxide; the molar ratio of the nickel salt to the selenium source is 1:1 to 2; the time of the second stirring is 1 to 3 h;

[0017] The mass concentration of carbon nanotubes in the aqueous dispersion of carbon nanotubes is 1 to 50 g / L; the volume ratio of the aqueous dispersion of carbon nanotubes to the volume of the mixed solution is 5:2 to 6; the mixing is carried out under stirring, and the time of the stirring is 0.5 to 3 h;

[0018] The temperature of the hydrothermal reaction is 120 to 180 °C, and the heat preservation time is 24 to 48 h.

[0019] The present invention also provides a polyurethane composite wave-absorbing material, which includes a polyurethane matrix and a filler filled in the polyurethane matrix;

[0020] The filler is the wave-absorbing material described in the above technical solution or the wave-absorbing material prepared by the preparation method described in the above technical solution.

[0021] Preferably, the mass percentage content of the filler in the polyurethane composite wave-absorbing material is 0.5 to 5%.

[0022] Preferably, the preparation raw materials of the polyurethane matrix include polyol, isocyanate and chain extender;

[0023] The polyol includes at least one of polytetrahydrofuran ether diol, propylene oxide polyether diol, polycaprolactone polyol and polyethylene glycol;

[0024] The isocyanate includes at least one of isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate;

[0025] The chain extender includes at least one of 2,2'-diaminodiphenyl disulfide, 4,4'-dithiobenzidine, 4,4'-dihydroxydiphenyl disulfide and 1,2-ethanedithiol.

[0026] The present invention also provides a preparation method of the polyurethane composite wave-absorbing material described in the above technical solution, which includes the following steps:

[0027] Dissolve the polyol and the isocyanate in an organic solvent, then add a catalyst for the third stirring, and then add a chain extender for the fourth stirring to obtain a polyurethane prepolymer;

[0028] Add the filler to the polyurethane prepolymer, perform the fifth stirring, and let the resulting system stand and cure successively to obtain the polyurethane composite wave-absorbing material.

[0029] Preferably, the molar ratio of the polyol, isocyanate and chain extender is 1:1-5:1-10;

[0030] The catalyst includes dibutyltin dilaurate; the dosage ratio of the polyol and the catalyst is 2 g: 0.05-0.2 mL.

[0031] Preferably, the temperature of the third stirring is 80 °C and the time is 2-6 h;

[0032] The temperature of the fourth stirring is 80 °C and the time is 2-6 h;

[0033] The mass ratio of the filler and the polyurethane prepolymer is 0.1-2:20;

[0034] The temperature of the fifth stirring is 80 °C and the time is 2-6 h;

[0035] The standing method is vacuum standing, and the standing time is 12-48 h;

[0036] The curing temperature is 60-100 °C and the time is 24-72 h.

[0037] The present invention provides a wave-absorbing material, including carbon nanotubes and selenides loaded on the carbon nanotubes; the selenides include nickel selenide and cobalt selenide; there is a heterojunction structure between the nickel selenide and the cobalt selenide.

[0038] In the present invention, heterostructures are formed between the selenides. This structure can effectively enhance the interfacial polarization of the material, promote the internal energy dissipation mechanism, enable electromagnetic waves to be quickly converted into heat and dissipated when passing through the heterojunction interface, can greatly optimize the electromagnetic wave absorption ability of the material. By introducing functional heterostructure selenides, the wave-absorbing material can not only significantly improve the electromagnetic wave absorption performance, but also maintain good environmental adaptability.

[0039] The present invention also provides a polyurethane composite wave-absorbing material, including a polyurethane matrix and a filler filled in the polyurethane matrix; the filler is the wave-absorbing material described in the above technical solution or the wave-absorbing material prepared by the preparation method described in the above technical solution.

[0040] As an excellent flexible polymer material, polyurethane exhibits excellent mechanical toughness, wear resistance, and environmental adaptability. As the matrix of flexible electromagnetic wave absorption materials, it can significantly enhance the flexibility and durability of composite materials. However, polyurethane has poor conductivity and low impedance matching, which limits its performance in electromagnetic wave absorption. The present invention adopts the composite form of functional fillers and polyurethane, which can effectively improve the electromagnetic wave absorption ability of the material.

[0041] Furthermore, reversible disulfide bonds are introduced into polyurethane through a chain extender to achieve the self-healing property of the material. This design can maintain the performance of the material during long-term use, reduce the replacement frequency, and thus improve economic efficiency and environmental friendliness.

[0042] The heterogeneous structure nickel cobalt selenide-carbon nanotubes / polyurethane composite electromagnetic wave absorption material provided by the present invention is prepared by a simple water bath method. Among them, the polyurethane material is a good polymer, and nickel cobalt selenide with excellent dielectric properties and highly conductive carbon nanotubes are introduced to form functional fillers, realizing controllable structure, effectively adjusting the dielectric constant of the composite material, improving impedance matching, further enhancing the electromagnetic wave absorption performance and full-band absorption of the composite material, meeting the requirements of various usage scenarios, and broadening its application range. Description of the Drawings

[0043] Figure 1 SEM image of NiSe 2 / CoSe 2 @CNTs-1 prepared in Example 1 and the electromagnetic wave absorption performance graph of NiSe 2 / CoSe 2 @CNTs / PU-1;

[0044] Figure 2 SEM image of NiSe 2 / CoSe 2 @CNTs-2 prepared in Example 2 and the electromagnetic wave absorption performance graph of NiSe 2 / CoSe 2 @CNTs / PU-2;

[0045] Figure 3 SEM image of NiSe 2 / CoSe 2 @CNTs-3 prepared in Example 3 and the electromagnetic wave absorption performance graph of NiSe 2 / CoSe 2 @CNTs / PU-3;

[0046] Figure 4 SEM image of NiSe 2 / CoSe 2 @CNTs-1 prepared in Example 1 and NiSe in2 / CoSe 2 SEM image of the microspheres. Specific implementation manners

[0047] The present invention provides a wave-absorbing material, comprising carbon nanotubes and a selenide loaded on the carbon nanotubes;

[0048] The selenide includes nickel selenide and cobalt selenide;

[0049] There is a heterojunction structure between the nickel selenide and the cobalt selenide.

[0050] In the present invention, the molar ratio of the nickel selenide to the cobalt selenide is preferably 1:1; the mass percentage content of the selenide in the wave-absorbing material is preferably 40-90%, specifically it can be 40%, 50%, 60%, 70%, 80%, 90%.

[0051] The present invention also provides a preparation method of the wave-absorbing material according to the above technical solution, comprising the following steps:

[0052] Disperse nickel salts and cobalt salts in water to obtain a dispersion;

[0053] Add ethylenediamine to the dispersion and perform a first stirring, then add a selenium source and perform a second stirring to obtain a mixed solution;

[0054] Mix the aqueous dispersion containing carbon nanotubes and the mixed solution, and perform a hydrothermal reaction to obtain the wave-absorbing material.

[0055] In the present invention, nickel salts and cobalt salts are dispersed in water to obtain a dispersion. In the present invention, the nickel salts preferably include at least one of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salts preferably include at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; the molar ratio of the nickel salts to the cobalt salts is preferably 1:1; the dispersion is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 0.5-3 h.

[0056] After obtaining the dispersion, in the present invention, ethylenediamine is added to the dispersion and a first stirring is performed, then a selenium source is added and a second stirring is performed to obtain a mixed solution. In the present invention, the molar ratio of the nickel salts to ethylenediamine is preferably 1:1.5-7.5; the time of the first stirring is preferably 1-3 h. In the present invention, the selenium source preferably includes at least one of sodium selenite and selenium dioxide; the molar ratio of the nickel salts to the selenium source is preferably 1:1-2; the time of the second stirring is preferably 1-3 h.

[0057] In the present invention, pre-complexation is carried out with ethylenediamine, introducing a large number of heterostructures during the hydrothermal synthesis of nickel cobalt selenide-carbon nanotubes, enhancing the interfacial polarization and electron dissipation ability of the material, further improving impedance matching, and achieving efficient absorption of electromagnetic waves. At the same time, the electromagnetic parameters can be regulated by changing the mass ratio of carbon nanotubes.

[0058] After obtaining the mixed solution, the present invention mixes the aqueous dispersion of carbon nanotubes and the mixed solution and performs a hydrothermal reaction to obtain the wave-absorbing material. In the present invention, the mass concentration of carbon nanotubes in the aqueous dispersion of carbon nanotubes is preferably 1-50 g / L. In the present invention, the aqueous dispersion of carbon nanotubes The liquid is preferably obtained by dispersing carbon nanotubes in water wherein the water is preferably deionized water, and the dispersion is preferably carried out in is carried out under ultrasonic conditions, and the ultrasonic time is preferably 1 h. In the present invention, the volume ratio of the aqueous dispersion of carbon nanotubes to the mixed solution is preferably 5:2-6; the mixing is preferably carried out under stirring conditions, and the stirring time is preferably 0.5-3 h.

[0059] In the present invention, the temperature of the hydrothermal reaction is preferably 120-180 °C, specifically 120 °C, 130 °C, 140 °C, 150 °C, 160 °C, 170 °C, 180 °C; the heat preservation time is preferably 24-48 h, specifically 24 h, 30 h, 36 h, 40 h, 48 h. In the present invention, after the hydrothermal reaction, it also preferably includes naturally cooling the obtained reaction system to room temperature and filtering, washing the filtered product alternately in absolute ethanol and deionized water, and vacuum drying the washed product; the number of times of alternate washing is preferably 3 times, the temperature of the vacuum drying is preferably 60-70 °C, and the time is preferably 24 h.

[0060] The present invention also provides a polyurethane composite wave-absorbing material, including a polyurethane matrix and a filler filled in the polyurethane matrix;

[0061] The filler is the wave-absorbing material described in the above technical solution or the wave-absorbing material prepared by the preparation method described in the above technical solution.

[0062] In the present invention, the mass percentage content of the filler in the polyurethane composite wave-absorbing material is preferably 0.5-5%, specifically 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.

[0063] In the present invention, the raw materials for preparing the polyurethane matrix preferably include polyol, isocyanate and chain extender; the polyol preferably includes at least one of polytetrahydrofuran ether glycol (PTMG), propylene oxide polyether glycol, polycaprolactone polyol and polyethylene glycol; the relative molecular weight of the polytetrahydrofuran ether glycol is preferably 1000 (i.e., PTMG1000); the isocyanate preferably includes at least one of isophorone diisocyanate (IPDI), 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate; the chain extender preferably includes at least one of 2,2'-diaminodiphenyl disulfide, 4,4'-dithiobenzidine, 4,4'-dihydroxydiphenyl disulfide and 1,2-ethanedithiol. In the present invention, the molar ratio of the polyol, isocyanate and chain extender is preferably 1:1-5:1-10.

[0064] The present invention also provides a method for preparing the polyurethane composite wave-absorbing material according to the above technical solution, comprising the following steps:

[0065] Dissolve the polyol and isocyanate in an organic solvent, then add a catalyst for the third stirring, and then add a chain extender for the fourth stirring to obtain a polyurethane prepolymer;

[0066] Add the filler to the polyurethane prepolymer, perform the fifth stirring, and the obtained system is sequentially allowed to stand and cured to obtain the polyurethane composite wave-absorbing material;

[0067] In the present invention, polyol and isocyanate are dissolved in an organic solvent, and then a catalyst is added for the third Stir, and then add a chain extender for the fourth stirring to obtain a polyurethane prepolymer. In the present invention, the organic solvent preferably includes N,N-dimethylformamide; the dosage ratio of the polyol to the organic solvent is preferably 0.002 mol:10 mL. In the present invention, the molar ratio of the polyol, isocyanate and chain extender is preferably 1:1-5:1-10. In the present invention, the dissolution in the organic solvent is preferably carried out under stirring, and the stirring time is preferably 0.5 h. In the present invention, the catalyst preferably includes dibutyltin dilaurate; the dosage ratio of the polyol to the catalyst is preferably 0.002 mol:60-100 μL; the temperature of the third stirring is preferably 80°C, and the time is preferably 2-6 h; the temperature of the fourth stirring is preferably 80°C, and the time is preferably 2-6 h.

[0068] After obtaining the polyurethane prepolymer, the present invention adds the filler to the polyurethane prepolymer, performs a fifth stirring, and the obtained system is sequentially allowed to stand and cured to obtain the polyurethane composite wave-absorbing material. In the present invention, the mass ratio of the filler to the polyurethane prepolymer is preferably 0.1-2:20; the temperature of the fifth stirring is preferably 80 °C, and the time is preferably 2-6 h; the standing method is preferably vacuum standing, and the standing time is preferably 12-48 h; the curing temperature is preferably 60-100 °C, and the time is preferably 24-72 h.

[0069] The chain extender adopted by the present invention introduces reversible disulfide bonds into the composite wave-absorbing material, realizing excellent flexibility and reparability; compared with other composite wave-absorbing materials, it has a longer service life, is more environmentally friendly and easy to repair; the obtained polyurethane composite wave-absorbing material can meet the requirements of multiple application environments.

[0070] The preparation method provided by the present invention is simple and fast, suitable for large-scale preparation, and an electromagnetic wave absorption composite material with excellent wave-absorbing performance can be obtained when the sample filling amount is 4 wt%. This composite material has obtained excellent reflection loss (-47.66 dB, f = 9.817 GHz, d = 2.97 mm) and excellent effective absorption bandwidth (4.2 GHz) in the frequency range of 8.2-12.4 GHz. The polyurethane composite wave-absorbing material provided by the present invention realizes the characteristics of strong flexibility and adaptability while meeting the requirements of thin thickness, strong absorption, and wide frequency band, and has a wide application prospect in the field of electromagnetic wave absorption.

[0071] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in this field.

[0072] Next, the technical solutions in the present invention will be clearly and completely described in conjunction with the embodiments in the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention without making creative efforts shall fall within the protection scope of the present invention.

[0073] Example 1

[0074] Disperse 1.625 mmol NiSO 4 ·6H 2 O and 1.625 mmol CoSO 4 ·6H 2 O in 20 mL of deionized water, and perform ultrasonic treatment for 0.5 h to obtain a dispersion;

[0075] Add 3.3 mL of ethylenediamine to the above-obtained dispersion, stir rapidly for 1 h, add 3.25 mmol of sodium selenite after mixing evenly, and stir vigorously for 1 h to obtain a mixed solution;

[0076] Disperse 0.47 g of carbon nanotubes in 20 mL of deionized water, and ultrasonically treat for 1 h to obtain an aqueous dispersion of carbon nanotubes. Add the aqueous dispersion of carbon nanotubes to the above-obtained mixed solution, stir for 0.5 h, and disperse evenly; then hydrothermally react the obtained mixed system at 180 °C for 24 h, naturally cool and then filter, and wash the product three times alternately with absolute ethanol and deionized water; finally, vacuum-dry the product at 60 °C for 24 h to obtain an electromagnetic wave absorbing material, denoted as NiSe 2 / CoSe 2 @CNTs-1, wherein the mass percentage content of the selenide in the electromagnetic wave absorbing material is 60%;

[0077] Dissolve 0.002 mol of PTMG1000 and 0.004 mol of IPDI in 10 mL of DMF, stir for 0.5 h, add 80 μL of dibutyltin dilaurate, and stir at 80 °C for 2 h; then add 0.49 g of 2,2'-diaminodiphenyl disulfide, and continuously stir at 80 °C for 2 h to obtain 3.329 g of a polyurethane prepolymer;

[0078] Add 0.138 g of the electromagnetic wave absorbing material to the polyurethane prepolymer, heat and stir at 80 °C for 2 h to mix evenly, place the mixed solution in a vacuum for 24 h, and finally cure at 80 °C for 48 h to obtain a polyurethane composite electromagnetic wave absorbing material, denoted as NiSe 2 / CoSe 2 @CNTs / PU-1, wherein the mass percentage content of the filler in the polyurethane composite electromagnetic wave absorbing material is 4%.

[0079] Example 2

[0080] Prepare the electromagnetic wave absorbing material in the same manner as in Example 1, except that the mass of the carbon nanotubes is 0.3 g, and the obtained electromagnetic wave absorbing material is denoted as NiSe 2 / CoSe 2 @CNTs-2, wherein the mass percentage content of the selenide in the electromagnetic wave absorbing material is 70%;

[0081] The obtained polyurethane composite electromagnetic wave absorbing material is denoted as NiSe 2 / CoSe 2 @CNTs / PU-2.

[0082] Example 3

[0083] Prepare the electromagnetic wave absorbing material in the same manner as in Example 1, except that the mass of the carbon nanotubes is 0.176 g, and the obtained electromagnetic wave absorbing material is denoted as NiSe 2 / CoSe 2 @CNTs-3, wherein the mass percentage content of the selenide in the electromagnetic wave absorbing material is 80%;

[0084] The obtained polyurethane composite microwave absorption material is denoted as NiSe 2 / CoSe 2 @CNTs / PU-3.

[0085] Performance test

[0086] Figure 1 For NiSe prepared in Example 1 2 / CoSe 2 @CNTs-1 SEM image and NiSe 2 / CoSe 2 @CNTs / PU-1 microwave absorption performance graph; as Figure 1 shown in (a), NiSe 2 / CoSe 2 is in the form of massive particles, evenly distributed and attached to the surface of CNTs; Figure 1 (b) and (c) are the three-dimensional and two-dimensional reflection loss (RL) graphs of NiSe 2 / CoSe 2 @CNTs / PU-1, and the specific test results are shown in Table 1;

[0087] Table 1 Microwave absorption performance of NiSe 2 / CoSe 2 @CNTs / PU-1

[0088] Minimum reflection loss RLmin Effective absorption bandwidth EAB 2.65 mm and 8.956 GHz frequency bands -17.19 dB 0.462 GHz 2.75 mm and 8.914 GHz frequency bands -18.34 dB 0.903 GHz 2.85 mm and 8.872 GHz frequency bands -18.91 dB 1.008 GHz 2.95 mm and 8.809 GHz frequency bands -19.12 dB 0.92 GHz 3.00 mm and 8.767 GHz frequency bands -19.04 dB 0.903 GHz

[0089] It can be seen that NiSe 2 / CoSe 2 @CNTs / PU-1 only obtains a minimum reflection loss of -19.12 dB and an effective absorption bandwidth of 0.92 GHz at 2.95 mm and 8.809 GHz bands.

[0090] Figure 2 For NiSe prepared in Example 2 2 / CoSe 2 @CNTs-2 SEM image and NiSe 2 / CoSe 2 @CNTs / PU-2 microwave absorption performance graph; as Figure 2 shown in (a), NiSe 2 / CoSe 2 The formed massive particles increase in size, and at the same time, more are attached to the surface and intertwined inside the CNTs, forming a good carbon conductive network; Figure 2 (b) and (c) are NiSe 2 / CoSe 2Three-dimensional and two-dimensional reflection loss (RL) diagrams of @CNTs / PU-2. The specific test results are shown in Table 2;

[0091] Table 2 NiSe 2 / CoSe 2 Absorbing properties of @CNTs / PU-2

[0092] Minimum reflection loss RLmin Effective absorption bandwidth EAB 2.78 mm and 10.972 GHz frequency bands -20.32 dB 2.982 GHz 2.88 mm and 9.901 GHz frequency bands -34.39 dB 3.549 GHz 2.97 mm and 9.817 GHz frequency bands -47.66 dB 4.2 GHz 3.27 mm and 9.523 GHz frequency bands -23.36 dB 3.633 GHz 3.48 mm and 9.901 GHz frequency bands -33.56 dB 1.701 GHz

[0093] It can be seen that NiSe 2 / CoSe 2 @CNTs / PU-2 only obtains an RLmin of -47.66 dB and an EAB of 4.2 GHz in the frequency bands of 2.97 mm and 9.817 GHz, covering the entire X band.

[0094] Figure 3 SEM diagram of NiSe 2 / CoSe 2 @CNTs-3 prepared in Example 3 and absorbing property diagrams of NiSe 2 / CoSe 2 @CNTs / PU-3; as shown in (a) of Figure 3 NiSe 2 / CoSe 2 aggregates to form NiSe 2 / CoSe 2 in the form of microspheres, that is, irregular polyhedral microspheres self-assembled from polycrystalline particles are uniformly mixed with CNTs; Figure 3 (b) and (c) of 2 are three-dimensional and two-dimensional reflection loss (RL) diagrams of NiSe 2 @CNTs / PU-3. The specific test results are shown in Table 3;

[0095] Table 3 NiSe 2 / CoSe 2 Absorbing properties of @CNTs / PU-3

[0096]

[0097]

[0098] It can be seen that NiSe 2 / CoSe 2 @CNTs / PU-3 only obtains an RLmin of -21.46 dB and an EAB of 2.604 GHz in the frequency bands of 3.16 mm and 10.069 GHz.

[0099] Figure 4 NiSe prepared in Example 12 / CoSe 2 @NiSe in CNTs-1 2 / CoSe 2 SEM image of the microspheres; as Figure 4 shown, microspherical NiSe 2 / CoSe 2 was successfully prepared by hydrothermal method, i.e., a polyhedral sphere aggregated by nanoparticles.

[0100] Comparative Example 1

[0101] Disperse 0.1 g of CNTMs in 10 mL of DMF and ultrasonically treat for 1 h to obtain a CNTMs dispersion;

[0102] Dissolve 2 g of PTMEG and 0.89 g of IPDI in 10 mL of DMF, stir for 0.5 h, add 80 μL of dibutyltin dilaurate, and stir at 80 °C for 2 h; then add 0.49 g of 2,2'-diaminodiphenyl disulfide and continue to stir at 80 °C for 2 h to obtain a polyurethane prepolymer;

[0103] Add the CNTMs dispersion to the polyurethane prepolymer, heat and stir at 80 °C for 2 h to mix evenly, place the mixed solution in vacuo for 24 h, and finally cure at 80 °C for 48 h to obtain a CNTs / PU composite material.

[0104] After testing, the minimum reflection loss of the CNTs / PU composite material is -32.59 dB at 3.01 mm and 9.219 GHz, and the effective absorption bandwidth is 2.54 GHz.

[0105] Comparative Example 2

[0106] Prepare the composite wave-absorbing material in the same manner as in Example 2, where the addition amount of ethylenediamine is 9.9 mL; after testing, the minimum reflection loss of the obtained polyurethane composite wave-absorbing material is -24.51 dB at 2.51 mm and 9.782 GHz, and the effective absorption bandwidth is 1.59 GHz.

[0107] Comparative Example 3

[0108] Disperse 1.625 mmol of NiSO 4 ·6H 2 O and 1.625 mmol of CoSO 4 ·6H 2 O in 20 mL of deionized water and ultrasonically treat for 0.5 h to obtain a dispersion;

[0109] Add 3.3 mL of ethylenediamine to the obtained dispersion, quickly stir for 1 h, add 3.25 mmol of sodium selenite after mixing evenly, and vigorously stir for 1 h to obtain a mixed solution;

[0110] The obtained mixed solution was subjected to hydrothermal reaction at 180 °C for 24 h, naturally cooled and then filtered, and the product was washed three times alternately with absolute ethanol and deionized water; finally, the product was vacuum dried at 60 °C for 24 h to obtain NiSe 2 / CoSe 2 ;

[0111] The polyurethane composite microwave absorbing material was prepared in the same manner as in Example 1, denoted as NiSe 2 / CoSe 2 / PU;

[0112] After testing, the minimum reflection loss of NiSe 2 / CoSe 2 / PU was -14.21 dB at 2.88 mm and 10.178 GHz, and the effective absorption bandwidth was 0.63 GHz.

[0113] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, rather than all embodiments. Other embodiments can be obtained according to this embodiment without creative efforts, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A wave absorbing material, characterized in that: It comprises carbon nanotubes and selenides supported on the carbon nanotubes; the selenides comprise nickel selenide and cobalt selenide; The nickel selenide and the cobalt selenide have a heterojunction structure.

2. The absorbing material according to claim 1, characterized in that: The molar ratio of nickel selenide to cobalt selenide is 1:1; The mass percentage of the selenide in the wave absorbing material is 40-90%.

3. The method for preparing the wave absorbing material according to claim 1 or 2, characterized in that: The following steps are involved: dispersing nickel salt and cobalt salt in water to obtain a dispersion; Adding ethylenediamine to the dispersion liquid and performing a first stirring, then adding a selenium source and performing a second stirring to obtain a mixed liquid; The aqueous dispersion containing carbon nanotubes and the mixed solution are mixed to carry out a hydrothermal reaction to obtain the wave absorbing material.

4. The preparation method according to claim 3, characterized in that: The nickel salt includes at least one of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt includes at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; the molar ratio of the nickel salt to the cobalt salt is 1:1; The dispersion is carried out under ultrasonic conditions, and the ultrasonic time is 0.5 to 3 hours; The molar ratio of the nickel salt to ethylenediamine is 1:1.5-7.5; the first stirring time is 1-3 hours; The selenium source includes at least one of sodium selenite and selenium dioxide; the molar ratio of the nickel salt to the selenium source is 1:1-2; the second stirring time is 1-3 hours; The mass concentration of carbon nanotubes in the aqueous dispersion containing carbon nanotubes is 1 to 50 g / L; the volume ratio of the aqueous dispersion containing carbon nanotubes to the mixed solution is 5:2 to 6; the mixing is carried out under stirring, and the stirring time is 0.5 to 3 hours; The temperature of the hydrothermal reaction is 120-180° C., and the insulation time is 24-48 hours.

5. A polyurethane composite absorbing material, characterized in that: It comprises a polyurethane matrix and a filler filled in the polyurethane matrix; The filler is the absorbing material according to claim 1 or 2 or the absorbing material prepared by the preparation method according to claim 3 or 4.

6. The polyurethane composite absorbing material according to claim 5, characterized in that: The mass percentage of the filler in the polyurethane composite wave-absorbing material is 0.5-5%.

7. The polyurethane composite absorbing material according to claim 5, characterized in that: The raw materials for preparing the polyurethane matrix include polyol, isocyanate and chain extender; The polyol comprises at least one of polytetramethylene glycol, propylene oxide polyether glycol, polycaprolactone and polyethylene glycol; The isocyanate comprises at least one of isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate and toluene diisocyanate; The chain extender includes at least one of 2,2'-diaminodiphenyl disulfide, 4,4'-dithiodiphenylamine, 4,4'-dihydroxydiphenyl disulfide and 1,2-ethanedithiol.

8. The method for preparing the polyurethane composite absorbing material according to any one of claims 5 to 7, characterized in that: The following steps are involved: Dissolving polyol and isocyanate in an organic solvent, then adding a catalyst and performing a third stirring, and then adding a chain extender and performing a fourth stirring to obtain a polyurethane prepolymer; The filler is added into the polyurethane prepolymer, and the fifth stirring is performed. The obtained system is allowed to stand and cured in sequence to obtain the polyurethane composite absorbing material.

9. The preparation method according to claim 8, characterized in that: The molar ratio of the polyol, isocyanate and chain extender is 1:1-5:1-10; The catalyst comprises dibutyltin dilaurate; the usage ratio of the polyol to the catalyst is 2g:0.05-0.2mL.

10. The preparation method according to claim 8, characterized in that: The third stirring temperature is 80°C and the time is 2 to 6 hours; The temperature of the fourth stirring is 80°C and the time is 2 to 6 hours; The mass ratio of the filler to the polyurethane prepolymer is 0.1 to 2:20; The fifth stirring temperature is 80°C and the time is 2 to 6 hours; The static method is vacuum static, and the static time is 12 to 48 hours; The curing temperature is 60-100° C. and the curing time is 24-72 hours.

Citation Information

Cited By

  • CoSe nanosheet composite-based light high-strength multifunctional polyurethane foam and preparation method thereof

    CN121379122A